Athletic Labor and Social Reproduction. (December 2019) - Kalman-Lamb, Nathan
This article connects the exploitation experienced by athletic laborers to sports fandom by theorizing athletic labor as a form of social reproductive labor. The work of athletes in high-performance spectator sport contributes to the affective reproduction of spectatorial subjects required by capitalism, albeit at a great cost to the laboring athlete. This intervention advances Marxist scholarship on the sociology of sport by extending the literature on social reproduction and labor into an entirely new and necessary sphere. Framing athletic labor as a form of social reproduction reveals that high performance spectator sport is more central to the political economy of late capitalism than is often understood and that sport is a more exploitative and dehumanizing site of labor even than conventional Marxist analysis has suggested.